Association between maxillary canine impaction and arch dimensions - Fattahi Hamidreza; Ghaeed Fatemeh; Alipour Abbas (Sciendo, 2012)
Objective: To compare palatal height index, arch width, and arch length characteristics in Iranian patients presenting with palatal and buccal canine impaction with a matched control group.